2018
DOI: 10.1186/s41983-018-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and vitamin D level in carpal tunnel syndrome patients

Abstract: BackgroundCarpal tunnel syndrome (CTS) is the most common entrapment neuropathy of the upper extremity. The aim of this study is to evaluate the body mass index (BMI) and vitamin D levels in CTS patients.MethodsThe current study was conducted at Zagazig University Hospitals. It included 50 CTS patients and 50 controls. Clinical assessment was carried out to exclude symptoms and signs of neuropathy. Laboratory investigations including vitamin D levels, glycosylated hemoglobin, liver, and kidney function were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
4
15
1
2
Order By: Relevance
“…CTS patients had significantly lower vitamin D levels compared with the controls. This observation was in agreement with previously published studies from Tanik et al (4), Nageeb et al (5) and Gürsoy et al (26). In contrast, Lee et al (27) showed there was no difference in vitamin D levels between the patients with CTS and the controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…CTS patients had significantly lower vitamin D levels compared with the controls. This observation was in agreement with previously published studies from Tanik et al (4), Nageeb et al (5) and Gürsoy et al (26). In contrast, Lee et al (27) showed there was no difference in vitamin D levels between the patients with CTS and the controls.…”
Section: Discussionsupporting
confidence: 93%
“…The association between parameters, such as sex, increased age, a high BMI and CTS have been reported in numerous studies. CTS patients have higher BMI values compared with controls (5,43,44), consistent with findings from the present study. Some 45.8% of patients with CTS were obese compared with 18.8% of the controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, most cases were mild and moderate in terms of CTS severity. Similar results were also found in many previous studies regarding severity [20][21][22]. We also observed that CTS was more severe among females.…”
Section: Discussionsupporting
confidence: 92%
“…Population at risk for this condition is women and age group of 40 to 60 5 . Some comorbid conditions are also found in CTS, such as obesity, diabetes mellitus, hypothyroid, and pregnancy 6 .…”
Section: Introductionmentioning
confidence: 99%